Azospirillum brasilense inoculation and nitrogen fertilization in a 3-year maize and black oat yield in succession - Piva, Jonatas Thiago; Schmitt, Djalma Eugênio; Fioreze, Samuel Luiz; Aparecida Guginski-Piva, Claudia; Ribeiro, Ricardo Henrique; Besen, Marcos Renan (Revista Ceres, 2023)
The objective of this work was to assess the effects of A. brasilense inoculation on seeds on the yield performance of maize and black oat as a function of nitrogen rate over a 3-year succession. The experiment was conducted from 2015 to 2018 under field conditions. Maize was grown for three growing seasons in rotation with two seasons of black oat at the same experimental site. A randomized block design with a split-plot arrangement was used. Main plots consisted of A. brasilense inoculation (inoculated and uninoculated plants) and subplots of four nitrogen rates (0, 40, 80, and 120 kg ha−1). Maize plants were evaluated for biometric parameters, yield, and yield components at flowering. Black oat plants were analyzed for dry matter yield at flowering. The inoculation of A. brasilense in maize and black oat seeds in succession does not promote productivity nor does it favor the nitrogen fertilization of these cultures.